Rocuronium vs. succinylcholine for rapid sequence intubation: a Cochrane systematic review2. (June 2017) - Tran, D. T. T.; Newton, E. K.; Mount, V. A. H.; Lee, J. S.; Mansour, C.; Wells, G. A.; Perry, J. J.
Summary: This systemic review was performed to determine whether rocuronium creates intubating conditions comparable to those of succinylcholine during rapid sequence intubation of the trachea. We searched the Cochrane Central Register of Controlled Trials (CENTRAL; 2015, Issue 2), MEDLINE (1966 to February Week 2 2015), and EMBASE (1988 to February 14 2015) for any randomised controlled trials or controlled clinical trials that reported intubating conditions comparing rocuronium and succinylcholine for rapid or modified rapid sequence intubation. The dose of rocuronium was at least 0.6 mg.kg −1 and succinylcholine was at least 1 mg.kg −1 . Sixty‐six studies were identified and 50 included, representing 4151 participants. Overall, succinylcholine was superior to rocuronium for achieving excellent intubating conditions (risk ratio (95%CI) 0.86 (0.81 to 0.92), n = 4151) and clinically acceptable intubation conditions (risk ratio (95%CI) 0.97 (0.95–0.99), n = 3992). A high incidence of detection bias amongst the trials coupled with significant heterogeneity means that the quality of evidence was moderate for these conclusions. Succinylcholine was more likely to produce excellent intubating conditions when using thiopental as the induction agent: risk ratio (95%CI) 0.81 (0.73–0.88), n = 2302) with or without the use of opioids (risk ratio (95%CI) 0.85 (0.78–0.93), n = 2292 or 0.85 (0.76–0.95), n = 1428). Abstract : ☛ CPD available athttp://www.learnataagbi.org